Motor adaptation and immediate retention to overground gait-slip perturbation training in people with chronic stroke: an experimental trial with a comparison group - Bhatt, Tanvi; Dusane, Shamali; Gangwani, Rachana; Wang, Shuaijie; Kannan, Lakshmi (Frontiers in Sports and Active Living, 2023)
Background Perturbation-based training has shown to be effective in reducing fall-risk in people with chronic stroke (PwCS). However, most evidence comes from treadmill-based stance studies, with a lack of research focusing on training overground perturbed walking and exploring the relative contributions of the paretic and non-paretic limbs. This study thus examined whether PwCS could acquire motor adaptation and demonstrate immediate retention of fall-resisting skills following bilateral overground gait-slip perturbation training. Methods 65 PwCS were randomly assigned to either (i) a training group, that received blocks of eight non-paretic (NP-S1 to NP-S8) and paretic (P-S1 to P-S8) overground slips during walking followed by a mixed block (seven non-paretic and paretic slips each interspersed with unperturbed walking trials) (NP-S9/P-S9 to NP-S15/P-S15) or (ii) a control group, that received a single non-paretic and paretic slip in random order. The assessor and training personnel were not blinded. Immediate retention was tested for the training group after a 30-minute rest break. Primary outcomes included laboratory-induced slip outcomes (falls and balance loss) and center of mass (CoM) state stability. Secondary outcomes to understand kinematic contributors to stability included recovery strategies, limb kinematics, slipping kinematics, and recovery stride length. Results PwCS within the training group showed reduced falls (p < 0.01) and improved post-slip stability (p < 0.01) from the first trial to the last trial of both paretic and non-paretic slip blocks (S1 vs. S8). During the mixed block training, there was no further improvement in stability and slipping kinematics (S9 vs. S15) (p > 0.01). On comparing the first and last training trial (S1 vs. S15), post-slip stability improved on both non-paretic and paretic slips, however, pre-slip stability improved only on the non-paretic slip (p < 0.01). On the retention trials, the training group had fewer falls and greater post-slip stability than the control group on both non-paretic and paretic slips (p < 0.01). Post-slip stability on the paretic slip was lower than that on the non-paretic slip for both groups on retention trials (p < 0.01). Conclusion PwCS can reduce laboratory-induced slip falls and backward balance loss outcomes by adapting their post-slip CoM state stability after bilateral overground gait-slip perturbation training. Such reactive adaptations were better acquired and retained post-training in PwCS especially on the non-paretic slips than paretic slips, suggesting a need for higher dosage for paretic slips. Clinical registry number NCT03205527